Optical Illusion, Neuro-Theological Examination and The Fall as desribed in Genesis and Matthew - Edward Sitepu; Slamet Triadi; David Ming; Yenny Gooltje; Milisi Sembiring (Pharos Journal of Theology)
This study examines the Fall of Man as described in the book of Genesis, portraying humanity’s transition from innocence to sin through disobedience to God. This foundational theological narrative significantly shapes Christian understandings of human nature, dignity, and redemption. By integrating neuro-theological insights with biblical accounts, the research explores the spiritual significance of Christ’s victory over Satan and its implications for human existence. Genesis offers a theological framework for understanding the human soul-body relationship, while the Gospels depict Christ’s redemptive work as the fulfillment of divine promises. The study applies neuro-theological principles to interpret the deceptive nature of optical illusions found in Genesis and Christ’s triumph over Satan in Matthew. It emphasizes that Satan seeks to destroy humanity— God’s image-bearers—through sensory deception and spiritual attack. Jesus counteracts these illusions by quoting Scripture, demonstrating the transformative power of God’s word. Employing a literature-based methodology, the study engages with both classical theological sources and contemporary neuro-theological discourse. Philip Yancey’s reflections on sensory distortion and spiritual perception provide a key reference, illustrating how artificial or indirect stimuli can shape human understanding and experience—paralleling the enemy’s deceptive strategies. This perceptual distortion is portrayed as a core tactic of Satan in corrupting human beings, as evidenced in Genesis 6 and reinforced by John 10:10a, where Satan is depicted as one who comes to steal, kill, and destroy. The findings suggest that theological narratives, when enriched by neuro- theological perspectives, offer deeper insight into Christ’s redemptive work and humanity’s spiritual struggle. This interdisciplinary approach enhances the understanding of biblical anthropology and the cosmic battle between good and evil.